Evaluation of first trimester serum soluble endothelial cell-specific tyrosine kinase receptor in normal and affected pregnancies. (13th October 2014) - Schneuer, Francisco J; Nassar, Natasha; Guilbert, Cyrille; Tasevski, Vitomir; Ashton, Anthony W; Morris, Jonathan M; Roberts, Christine L
Abstract: Aims : To assess soluble endothelial cell-specific tyrosine kinase receptor (sTie-2) levels in the first trimester of pregnancy and its association with adverse pregnancy outcomes; and examine the predictive accuracy. Study design : In this nested case-control study, serum sTie-2 levels were measured in 2616 women with singleton pregnancies attending first trimester screening in New South Wales, Australia. Multivariate logistic regression models were used to assess the association and predictive accuracy of serum sTie-2 with subsequent adverse pregnancy outcomes. Results : Median (interquartile range) sTie-2 for the total population was 19.6 ng/ml (13.6–26.4). Maternal age, weight, and smoking status significantly affected sTie-2 levels. There was no difference in serum sTie-2 between unaffected and women with adverse pregnancy outcomes. After adjusting for maternal and clinical risk factors, low sTie-2 (<25th centile) was associated with preeclampsia (Adjusted odds ratio: 1.61; 95% CI: 1.01–2.57), however, the accuracy of sTie-2 in predicting preeclampsia was not different from chance (AUC = 0.54; p  = 0.08) and does not add valuable predictive information to maternal and clinical risk factors. Conclusions : Our findings suggest that low sTie-2 levels are associated with preeclampsia, however, it does not add valuable information to clinical and maternal risk factor information in predicting preeclampsia or any other adverse pregnancy outcomes.